MicroRNAs – Important Molecules in Lung Cancer Research - Leidinger, Petra; Keller, Andreas; Meese, Eckart (Frontiers in Genetics, 2012)
MicroRNAs (miRNA) are important regulators of gene expression. They are involved in many physiological processes ensuring the cellular homeostasis of human cells. Alterations of the miRNA expression have increasingly been associated with pathophysiological changes of cancer cells making miRNAs currently to one of the most analyzed molecules in cancer research. Here we provide an overview of miRNAs in lung cancer. Specifically, we address biological functions of miRNAs in lung cancer cells, miRNA signatures generated from tumor tissue and from patients’ body fluids, the potential of miRNAs as diagnostic and prognostic biomarker for lung cancer, and its role as therapeutical target.